Test No. 226: Predatory mite (Hypoaspis (Geolaelaps) aculeifer) reproduction test in soil (OECD Guidelines for the Testing of Chemicals, Section 2, 2016)
This Test Guideline describes a method to assess the effects of chemical substances in soil on the reproductive output of the soil mite species Hypoaspis (Geolaelaps) aculeifer Canestrini (Acari: Laelapidae). It can be used for water soluble or insoluble substances, but not with volatile substances. Adult females of similar age are exposed to a range of concentrations of the test substance mixed into 20 g dry mass of artificial soil 28-35 days after the start of the egg laying period. Depending on the endpoint (ECx, NOEC or both), five to twelve concentrations should be tested. At least two to four replicates for each test concentrations and six to eight control replicates, of 10 animals each, are recommended. At 20¡ãC, the test lasts 14 days after introducing the females, which usually allows the control offspring to reach the deutonymph stage. The number of surviving females (mortality ¡Ü 20% for a valid test) and the number of juveniles per test vessel (at least 50 for a valid test) are determined. The fecundity of the mites exposed to the test substance is compared to that of controls in order to determine the ECx (e.g. EC10, EC50) or the No Observed Effect Concentration (NOEC). Any observed differences between the behaviour and the morphology of the mites in the control and the treated vessels should be recorded